Divergent effects of detachment from work: a day-level study on employee creativity. Issue 2 (4th March 2017) - Niks, Irene M. W.; de Jonge, Jan; Gevers, Josette M. P.; Houtman, Irene L. D.
ABSTRACT: Detachment from work during non-work time is generally related to a decrease in work-related strain. However, it might also hamper employees' generation of new and useful ideas about work by completely shutting off work-related thoughts and/or feelings outside of work. In this day-level study, we used a within-person design to investigate the role of cognitive and emotional detachment from work during non-work time in relation to equivalent types of job demands and job resources, in the prediction of employee creativity. Cognitive detachment from work refers to mentally disconnecting from work and no longer thinking about job-related issues, whereas emotional detachment from work refers to affectively disconnecting from work and no longer experiencing job-related emotions. Survey data were gathered over the course of eight consecutive days from 151 health care employees. Multi-level analyses revealed that: (1) cognitive detachment was positively related to creativity, irrespective of the level of cognitive job demands and resources; (2) high emotional job demands in combination with either low levels of emotional detachment or high levels of emotional job resources were positively related to creativity. This day-level study provides insight into the relation between detachment from work and creativity from a process perspective, by showing specific conditions under which different types of detachment from work benefit employee creativity.